Perimenopause Amelioration of a TCM Recipe Composed of Radix Astragali, Radix Angelicae Sinensis, and Folium Epimedii: An In Vivo Study on Natural Aging Rat Model. (16th December 2013) - Su, Ji-Yan; Xie, Qing-Feng; Liu, Wei-Jin; Lai, Ping; Liu, Dan-Dan; Tang, Li-Hai; Dong, Tina T. X.; Su, Zi-Ren; Tsim, Karl W. K.; Lai, Xiao-Ping; Li, Kun-Yin
Abstract : Traditional Chinese medicine (TCM) has been extensively applied as preferable herbal remedy for menopausal symptoms. In the present work, the potential of a TCM recipe named RRF, composed of Radix Astragali, Radix Angelicae Sinensis, and Folium Epimedii, was investigated on a natural aging rat model. After administration of RRF (141, 282, and 564 mg/kg/d), the circulated estradiol (E2 ) level increased accompanied by a reduction of serum follicle stimulating hormone (FSH). But no significant impact on serum lutenizing hormone (LH) level was observed. As a result of the E2 -FSH-LH adjustment, the histomorphology degenerations of ovary, uterus, and vagina of the 11.5-month female rats were alleviated. And lumbar vertebrae trabecular microstructure was also restored under RRF exposure by means of increasing the trabecular area and area rate. Moreover, levels of hypothalamic dopamine (DA) and norepinephrine (NE) rallied significantly after RRF treatment. Results from our studies suggest that RRF possesses a positive regulation on the estrogen imbalance and neurotransmitter disorder, thereby restoring reproductive organ degeneration and skeleton deterioration. The above-mentioned benefits of RRF on the menopause syndromes recommend RRF as a potential candidate for the treatment of perimenopausal syndrome.